Leukotriene signaling as molecular correlate for cognitive heterogeneity in aging: an exploratory study - Mrowetz, Heike; Kotob, Mohamed H.; Forster, Jennifer; Aydin, Iren; Unger, Michael Stefan; Lubec, Jana; Hussein, Ahmed M.; Malikovic, Jovana; Feyissa, Daniel Daba; Korz, Volker; Höger, Harald; Lubec, Gert; et al. (Frontiers in Aging Neuroscience, 2023)
Aging is in general associated with a decline in cognitive functions. Looking more closely, there is a huge heterogeneity in the extent of cognitive (dys-)abilities in the aged population. It ranges from the population of resistant, resilient, cognitively unimpaired individuals to patients with severe forms of dementias. Besides the known genetic, environmental and life style factors that shape the cognitive (dys-)abilities in aging, the underlying molecular mechanisms and signals related to cognitive heterogeneity are completely unknown. One putative mechanism underlying cognitive heterogeneity might be neuroinflammation, exerted through microglia, the brain’s innate immune cells, as neuroinflammation is central to brain aging and neurodegenerative diseases. Recently, leukotrienes (LTs), i.e. small lipid mediators of inflammation produced by microglia along aging and neurodegeneration, got in the focus of geroscience as they might determine cognitive dysfunctions in aging. Here, we analyzed the brain’s expression of key components of the LT synthesis pathway, i.e. the expression of 5-lipoxygenase (5-Lox), the key enzyme in LT production, and 5-lipoxygenase-activating protein (FLAP) in young and aged rats. More specifically, we used a cohort of rats, which, although grown up and housed under identical conditions, developed into aged cognitively unimpaired and aged cognitively impaired traits. Expression of 5-Lox was increased within the brain of aged rats with the highest levels detected in cognitively impaired animals. The number of microglia cells was higher in the aged compared to the young brains with, again, the highest numbers of 5-Lox expressing microglia in the aged cognitively impaired rats. Remarkably, lower cognitive scores in the aged rats correlated with higher numbers of 5-Lox positive microglia in the animals. Similar data were obtained for FLAP, at least in the cortex. Our data indicate elevated levels of the LT system in the brain of cognitively impaired animals. We conclude, that 5-Lox expressing microglia potentially contribute to the age-related cognitive decline in the brain, while low levels of the LT system might indicate and foster higher cognitive functions and eventually cognitive reserve and resilience in aging.